Legibility of neighborhood parks as a predicator for enhanced social interaction towards social sustainability - Moulay, Amine; Ujang, Norsidah; Said, Ismail (Elsevier, 2017)
Researchers commonly acknowledge the functions of neighborhood parks in terms of social interaction and their potential roles as social integrators. Nevertheless, many cities are facing the problem of underutilized parks which could be due to the park elements that are not legible and appealing. This paper examines the relationship between legibility attributes (clear structure, visual obstacles, and accessibility) with social interaction (park engagement and the intensity of contact) within neighborhood parks. To confirm the extent to which legibility attributes predict social interaction, surveys were conducted with 378 participants in the neighborhoods of Putrajaya, Malaysia. Results revealed that legibility of the neighborhood parks influences duration of use, which in turn increases the potential for social interactions among neighborhood residents. The level of visual obstruction was strongly linked with the quality of the edges and distances between park activities. The findings highlight the importance of legibility in the planning and design of public spaces to encourage residents to stay longer while enhancing interaction in neighborhood parks and ultimately achieving social sustainability.